Tandem catalysis by in-situ generated microporous COF-Pd nanoparticle hybrids - Bhadra, Mohitosh; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: covalent organic frameworks; Pd nanoparticles; tandem catalysis

CO oxidation on large high-index faceted Pd nanostructures - Sreedhala, S.; Sudheeshkumar, V.; Vinod, C. P. (Journal of Catalysis, 2016)
The structure sensitivity of CO oxidation has been investigated on oxide-supported palladium nanoparticles of different morphologies. The reactivity of concave nanocubes and nanoflowers that expose {3 1 0} and {3 1 1} high-index facets showed a lower onset temperature for CO oxidation than Pd nanospheres of size around 6 nm. These concave nanocubes and nanoflowers were also found to catalyze the CO oxidation reaction more efficiently than simple cubes and spheres of similar size that exposed low-index facets. The enhanced activity of these nanoparticles compared with other morphologies are attributed to the presence of sites of under-coordination on the exposed high-index facets. The larger nanoparticles were also found to be more stable in the reaction environment. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: CO oxidation; High-index facets; Pd nanoparticles; structure sensitivity

CO2 hydrogenation to formate by palladium nanoparticles supported on N-incorporated periodic mesoporous organosilica - Betsy, K. J.; Lazar, Anish; Pavithran, Anjuna; Vinod, C. P. (ACS Sustainable Chemistry & Engineering, 2020)
Development of a heterogeneous catalyst capable of selective transformation of CO2 to valuable products still remains a challenge. In this article, we account for the surfactant-directed synthesis of a new framework-incorporated nitrogen-containing periodic mesoporous organosilica nanosphere (NPMO). A thoroughly characterized N-incorporated hybrid PMO was utilized as a platform for stabilizing well-dispersed and easily accessible Pd nanoparticles (Pd-NPMO) without using any stabilizing agents or expensive dendrimers. Further, this bifunctional hybrid catalyst has been demonstrated to heterogeneously catalyze aqueous phase CO2 hydrogenation (CO2/H-2 ratio 1:3) for the direct synthesis of formate under 4 MPa pressure and at 100 degrees C. To validate the superior performance of the Pd-NPMO catalyst, we compared the activity with Pd-SBA-15 catalysts, and the results showed a 10-fold increase in turnover frequency of 108 h(-1) using Pd on NPMO which envisaged the crucial role of nitrogen sites in this catalyst to boost the CO2 valorization to formate.
Keywords: CO2 hydrogenation; Formic acid synthesis; Hybrid silica; Pd nanoparticles; PMO

Spectroscopic evidences for the size dependent generation of pd species responsible for the low temperature CO oxidation activity on Pd-SBA-15 nanocatalyst - Soni, Yogita; Pradhan, Sumanta; Bamnia, Mahesh K.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.; Khan, Tuhin Suvra; Haider, M. A.; Vinod, C. P. (Applied Catalysis B-Environmental, 2020)
A comprehensive size dependent CO oxidation activity has been demonstrated for Pd-SBA-15 catalysts with Pd NPs of varying sizes such as 1-2, 4-6 and 7-10 nm. Pd-SBA-15 catalyst with smallest sized NPs (Pd-S-N) has been synthesized by modified deposition precipitation method recently developed in our lab. Pd-S-N catalyst (reduced at 400 degrees C) demonstrated CO oxidation activity with lower light off temperature (50 degrees C), clearly one of the best reported for a Pd-silica system. A detailed XPS and in-situ DRIFTS analyses further supported by XAS and DFT calculations reveal the presence of easily decomposable highvalent Pd-oxide on co-ordinatively unsaturated Pd sites (Pdcus). Weak binding of CO on Pdcus sites in small Pd NPs leaving sites for oxygen activation is attributed to the low temperature activity of Pd-S-N for CO oxidation.
Keywords: CO oxidation; high-valent Pd species; Pd nanoparticles; SBA-15; under coordinated Pd atoms

Ultra-small Pd nanoparticles on SBA-15: an efficient catalyst for one-pot reductive alkylation of nitrobenzene with size-dependent activity - Soni, Yogita; Philip, Milda C.; Vinod, Chathakudath P. (Topics in Catalysis, 2025)
One-pot reductive alkylation of nitrobenzene with alcohol is an important organic synthesis reaction to form 2 degrees amines. In the present work, we have demonstrated that Pd/SBA-15 can be an effective catalytic system for this reaction. We have designed ultra-small Pd nanoparticles supported on SBA-15 for the synthesis of secondary amine, N-ethylaniline, through one-pot reductive alkylation of nitrobenzene with ethanol under ambient conditions. Ethanol functions both as the alkylating agent and the solvent in this process. The reaction is driven by the simultaneous hydrogenation of nitrobenzene to aniline, dehydrogenation of ethanol to aldehyde, and condensation of aniline and acetaldehyde to form N-ethylaniline. The size of the Pd nanoparticles plays a decisive role in the product selectivity. The undercoordinated sites present on ultra-small Pd NPs can facilitate ethanol dehydrogenation to acetaldehyde, thereby enhancing the selectivity towards N-ethylaniline compared to larger Pd nanoparticles. We have also studied the effect of different mesoporous supports such as SBA-15, MCM-41, and KIT-6 on the N-ethylaniline selectivity and found that SBA-15 was most selective. We have demonstrated that by carefully designing the catalyst such as controlling the Pd NPs size to obtain the maximum quantity of undercoordinated sites and choosing suitable support, the aliphatic alcohols can also be used for reductive alkylation of nitrobenzene in one-pot with optimum yields of N-alkylaniline.
Keywords: KIT-6; MCM-41; Modified deposition precipitation; nitrobenzene; Pd nanoparticles; Reductive alkylation; SBA-15; secondary amines; Undercoordinated Pd sites